RISIKO DEHUMANISASI PADA CROWDFUNDING SEBAGAI AKSES PENDANAAN BERBASIS TEKNOLOGI DI INDONESIA - Gita Widi Bhawika (Institut Teknologi Sepuluh Nopember, 2017)
Crowdfunding is a new phenomena. This fundraising based technology has increased in popularity since a decade ago. Crowdfunding can help people to fund their initiatives workings without boundaries because it only need internet connection to ask and give money. It is not necessary to gain relationship between initiator and funder. Yet, from the conventional fundraising point of view, it is important to build relationship in increasing the loyal funder who can easily fund the future initiator’s initiatives. Thus, crowdfunding has a potential dehumanization risk. This descriptive research will discuss about crowdfunding in Indonesia, and its dehumanization risks. Moreover, this paper will propose the model of donor relationship management to minimize the dehumanization risk.